The Relationship Of Stress Level With Menstrual Cycle In Health Students At Poltekkes Kemenkes Semarang - Windha Mellynia; Sri Sumarni; Agustin Setianingsih (Journal of Applied Health Management and Technology, 2022)
ABSTRACT          Stress triggers 4.7 times the risk and abnormal nutritional status triggers 2.8 times the risk of experiencing irregular menstrual cycle1. Stress level is one of the factors that affect the menstrual cycle and is often felt by final year health students. The purpose of this study was to determine the relationship between stress levels and the menstrual cycle in health students at Poltekkes Kemenkes Semarang. This type of research is quantitative analytic with cross sectional design. The sampling method used simple random sampling with a sample size of 131 respondents. The results of the study based on the Spearman-rho test showed that there was a relationship between stress levels and the menstrual cycle, p-value = 0.037 (p-value 0.05). The value of r or correlation coefficient is 0.182 means that the level of strength of the correlation between stress levels and the menstrual cycle in final year health students at Poltekkes Kemenkes Semarang is a weak correlation. While the positive relationship contained in the correlation coefficient means that the direction of the relationship is unidirectional, namely the increasing stress level, the more irregular or abnormal menstrual cycle. The conclusion of this study is that there is a relationship between stress levels and the menstrual cycle in health students at Poltekkes Kemenkes Semarang.